RESEARCH ADVANCE OF 3-HYDROXY-3-METHYLGLUTARYL-COENZYME A SYNTHASE IN PLANT ISOPRENOID BIOSYNTHESIS - J. Chang; Y. Ning; F. Xu; S. Cheng; X. Li (Journal of Animal and Plant Sciences, 2015)
Terpenoids are synthesized in plants via the mevalonate (MVA) and the methylerythritol phosphate (MEP) pathways, with isopentenyl diphosphate (IPP) as the main intermediate metabolite. 3-Hydroxy-3-methylglutaryl-Coenzyme A synthase (HMGS) is the second enzyme in MVA pathway of isoprenoid biosynthesis, and catalyzes the condensation of acetyl-CoA with acetoacetyl-CoA to yield HMG-CoA.A growing body of evidence now indicates that HMGS plays significant roles in biosynthesis of terpenoids in plants. The sequences and structures of HMGS genes isolated from most plants are highly homologous. HMGS has been found to be expressed in most organs of plants, and its expression correlates strongly with accumulation of terpenoids in plants. This review focus on the research progress in the biological significance, protein structure, regulatory mechanism, gene characterization and functional analysis of HMGS in plant. The studies on the gene family encoding HMGS has provided valuable insights into its function, phylogeny, and regulation of terpenoid content in plants.
Keywords: Terpenoids; HMGS; HMG-CoA; biosynthetic pathway; expression